PENGARUH STRATEGI PEMBELAJARAN AKTIF TIPE GIVING QUESTION AND GETTING ANSWER (GQGA) TERHADAP PRESTASI BELAJAR MATEMATIKA PADA SISWA KELAS V SDN 07 PAGI KECAMATAN DUREN SAWIT - Dewi, Bugi Kurnia; Afifa Azzahra, Riska Mutia; Allifa, Qanita Nur; Marini, Arita (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
This study aims to determine the effect of the Active Learning Strategy Type of Asking Questions and Getting Answers (GQGA) on the mathematics achievement of fifth grade elementary school students in Duren Sawit District. This type of research is Quasi Experimental (pseudo-experimental) with a post-test design. The population in this study were all of the fifth graders of elementary school in Duren Sawit District, totaling 67 students. Sampling was done by total sampling technique. The data obtained were analyzed in two stages, namely descriptive analysis and inferential analysis. The results showed that the proportion of completeness in the experimental class taught using the active learning model of the Giving Question and Getting Answers type was higher in the subject matter of nomenclature of compounds and description reaction equations. This can be seen from the learning process which contains game elements so that students do not feel bored in the learning process.